Amiodarone-associated optic neuropathy in the treatment of cardiovascular diseases - E. E. Ioyleva; N. A. Gavrilova; A. V. Zinov’eva; M. V. Kats (Российский офтальмологический журнал, 2020)
An increase in the growth of cardiovascular diseases has been observed in the last few years. Cardiac rhythm disturbances, especially atrial fibrillation, in absence of cardioversion and proper prophylaxis lead to thromboembolic complications. Drug therapy in rhythm disorders consists of the many antiarrhythmic drugs, prescribed for a long period of time. This fact can result to the ocular toxicy, which have insidious and slow progression. First and foremost, there is a risk of amiodarone-associated toxicity. Amiodarone affects as anterior segment structures (photosensitivity, corneal and conjunctiva deposits, anterior subcapsular cataract) as posterior segment structures (optic neuropathy). Fibers of the papillomacular bundle are the most vulnerable structures in optic nerve to the toxic effect of amiodarone due to the absence of myelination and salutatory conduction, their small size and high-energy requirements. The difficulties in diagnosis of amiodarone-associated optic neuropathy are related to slow progression (patients don’t notice symptoms until the late stages) and clinical similarity to ischemic optic neuropathy.